Research on preservation and renewal strategies for historic districts under space syntax - Wang Yawen; Wang Yanjun (ITM Web of Conferences, 2025)
Historic districts are an integral part of urban communities, and due to the unique nature of their living heritage, they face the contradiction between preservation and development, necessitating the identification of suitable renewal models and strategies. This study focuses on Sifang Road historic district in Qingdao. It applies space syntax for quantitative analysis of the district's street and alley spaces, including measures of connectivity, control, average depth, comprehensibility, and visual integration. Taking into account the development challenges of Sifang Road historic district, this research explores micro-renewal strategies for the historic district. This study aims to enhance urban vitality, protect and renew historic districts, and demonstrate the potential of using space syntax for urban renewal, providing ideas and methods for the preservation and renewal of historic districts.